Application of the Learning Vector Algorithm Quantization On Smart Barcodes - Andre Andre; Achmad Fauzi; Milli Alfhi Syari (Indonesian Journal of Education And Computer Science, 2023)
The implementation of the Learning Vector Quantization (LVQ) algorithm on smart barcodes aims to enhance efficiency and accuracy in recognizing and tracking product data. In this context, barcodes serve as visual representations containing crucial product information. The LVQ algorithm is employed to optimize the classification and matching processes of barcode data with precise references. Through repeated training, this algorithm adapts learning vectors to better recognize barcode variations. In this study, researchers analyze the impact of LVQ algorithm implementation on smart barcode systems concerning identification accuracy, computational efficiency, and adaptability to changes. Experimental results demonstrate the significant benefits of applying barcodes to inventory systems in overall stock management and business efficiency. By utilizing barcode technology, the processes of tracking and recording product data become faster, more accurate, and automated. Barcode usage minimizes human errors, optimizes time, and reduces operational costs. By combining the intelligence of the LVQ algorithm with the potential of barcodes, this research illustrates a crucial advancement in the technology integration domain for the development of more sophisticated and effective systems